2019
DOI: 10.5455/aim.2019.27.300-304
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Health Information Systems Through the Perspective of Computer Engineering Students and Medical Students

Abstract: Introduction: Computer Engineering Students (CES) and Medical Students (MS) will actively participate in the management of health information system in the future. Aim: The aim of the study was to evaluate the views of CES and MS about the patient privacy and security of health information systems. Methods: The participants of this cross-sectional study were the 3 rd and 4 th year CES of Marmara University, (n=163, F/M:71/92) and the 5 th and 6 th year MS of Marmara University (n=65, F/M:38/27). The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is increasingly well-established that appropriate data should support OSH for HWs at all its stages [ 47 , 48 ]. Computerised information is known to improve the quality of health information, due to increased speed, integration of data and easy access to all sources [ 49 ]; studies have shown that web-based systems improve data completeness and data accuracy [ 41 , 50 ], albeit there is abundant evidence that most information systems fail in their actual use. As such research on how implementation is conducted is essential to ensure successful implementation and sustainable use [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly well-established that appropriate data should support OSH for HWs at all its stages [ 47 , 48 ]. Computerised information is known to improve the quality of health information, due to increased speed, integration of data and easy access to all sources [ 49 ]; studies have shown that web-based systems improve data completeness and data accuracy [ 41 , 50 ], albeit there is abundant evidence that most information systems fail in their actual use. As such research on how implementation is conducted is essential to ensure successful implementation and sustainable use [ 51 ].…”
Section: Discussionmentioning
confidence: 99%